Primate neuroethology - Platt, Michael L.; Ghazanfar, Asif A. (New York ; Oxford : Oxford University Press, 2010)
This edited volume bridges the epistemological gap between primate ethologists and primate neurobiologists. Leading experts in several fields will review work ranging from primate foraging behaviour to the neurophysiology of motor control, from vocal communication to the functions of the auditory cortex.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Primates -- Nervous system; Primates -- Psychology; Primates -- Behavior